The Reliability and Validity of Quality of Life Questionnaire Upper Limb Lymphedema (ULL-27) Turkish Patient With Breast Cancer Related Lymphedema - Kayali Vatansever, Ayşe; Yavuzşen, Tuğba; Karadibak, Didem (Frontiers in Oncology, 2020)
Purpose: Breast cancer is the most common cancer amongst women both in Turkey and in the world. Lymphedema, which negatively affects the quality of life, is one of the most prevalent problems reported by breast cancer survivors. Upper Limb Lymphedama 27 (ULL-27) questionnaire is a valid and reliable tool that assesses the quality of life in patients with breast cancer-related lymphedema. Until now, a Turkish-language version was lacking. The aim of this study was to perform a cross-cultural validation and reliability of the Turkish version of the ULL-27 questionnaire. Methods: This cross-sectional study involved forward- backward translation, and cross-cultural adaptation. 81 women (mean age and body mass index 54.96 ± 11.35 years and 29.50 ± 5.74 kg/m2) who had breast cancer related-upper extremity lymphedema were evaluated using the ULL-27 Quality of life questionnaire-Turkish version. Assessment of limb size was quantified by using circumferential limb measurements. European Organization for Research and Treatment of Cancer (EORTC) 30-item Quality of Life Questionnaire and Quality of Life Questionnaire breast cancer-23 (QLQ-BR23) were analyzed by Pearson's correlation analysis with the ULL-27 Turkish Version to indicate the convergent validity. Cronbach's alpha (internal consistency) and exploratory factor analysis were used to assess the questionnaire's reliability. Results: The mean of lymphedema duration and severity were 23.12 ± 30.88 months. Mild lymphedema was reported in 42% (34 people) of the cases included in the study. It was observed that 33.3% (27 people) had moderate lymphedema and 24.7% (20 people) had severe lymphedema. The alpha coefficient (internal consistency) for the Turkish ULL-27 total score was high (alpha = 0.93). Content validity was good because all questions were understandable for all participants (The alpha coefficient for the subgroups of the scale of physical, psychological, social scores, were 0.90, 0.87, and 0.75, respectively). External construct validity was highly confirmed by expected correlations with comparator scales, EORTC-30, and QLQ-BR23 (p < 0.01). Conclusions: The Turkish version of the ULL-27 Questionnaire is a valid and reliable tool for evaluating QoL in women with upper limb lymphedema related to breast cancer.